Influence of e-counselling skills, ethics, and limitations on counselling self-efficacy among e-counsellors in Malaysia - Asri, Alia Sarah (2022)
Consistent with an increased acceptance of e-counselling in Malaysia, there is a need for e-counsellors who have high self-efficacy in carrying out e-counsellingrelated tasks. However, current studies lack empirical data that identifies counselling self-efficacy among e-counsellors in Malaysia. The purpose of this study is to identify the influence of e-counselling skills, e-counselling ethics and e-counselling limitations on counselling self-efficacy among e-counsellors in Malaysia. A correlational study design was employed, and 233 e-counsellors from various public and private institutions in Malaysia were selected using a simple random sampling procedure. Through emails, respondents were given an access link to an online survey form containing five sections: (i) demographic information, (ii) e-counselling skills questionnaire, (iii) e-counselling ethics questionnaire, (iv) e-counselling limitations questionnaire, and (iv) Counselling Self-Estimate Inventory (COSE). Analysis of the descriptive indicated high levels for all variables except counselling self-efficacy (moderate level). Analysis of inferential using Pearson correlation reported a positive correlation between ecounselling skills and counselling self-efficacy, as well as between e-counselling ethics and counselling self-efficacy. E-counselling limitations reported a negative correlation with counselling self-efficacy. Finally, a multiple regression analysis reported that the independent variables significantly influenced counselling selfefficacy. E-counselling skills was reported as the best predictor of counselling self-efficacy, followed by e-counselling limitations. The findings from this study are pertinent to support more research investigating e-counselling in the Malaysian context, and provide suggestions for the professional counselling associations, counselling programme providers, counselling educators and professional counsellors to improve the training and delivery of e-counselling services in Malaysia.